Penerapan Personal Selling PT.PGN Area Bekasi Dalam Menarik Minat Beli Pelanggan Rumah Tangga - Abdul Aziz Pamungkas; Jamiati KN (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
In the world of marketing, the high level of marketing of diverse products is a problem or challenge for the marketing division in every company in terms of market competition. The research entitled "Application of Personal Selling PT. PGN Bekasi Area in Attracting the Interest of Household Customers" has the aim of applying personal selling, inhibiting and supporting factors, and stages of personal selling PT. PGN Bekasi Area in attracting the interest of household customers. The theories used in this research are marketing communication theory, marketing communication mix, personal selling and buying interest, where this research uses descriptive methods with qualitative research and data collection techniques using structured interviews, observation and data triangulation. When the data obtained has been collected, it is then analyzed by reducing the data, presenting it, and verifying or checking again. From the research stages carried out, the results of the research can be seen that the application of personal selling carried out by PT. PGN Area Bekasi in attracting customer interest starts from approaching areas that have natural gas pipeline infrastructure, making it available to local regional heads (RW) to socialize natural gas, then carry out personal selling which is packaged in a natural gas socialization. Natural gas socialization stages include approach, presentation, overcoming objections, closing the sale and follow-up. The factors that can attract customer interest include product quality factors, brand factors, packaging factors, price factors, product availability factors and promotional factors.